2020
DOI: 10.1007/s00049-020-00321-5
|View full text |Cite
|
Sign up to set email alerts
|

Do plant volatiles confuse rather than guide foraging behavior of the aphid hyperparasitoid Dendrocerus aphidum?

Abstract: Many species of parasitoid wasps use plant volatiles to locate their herbivorous hosts. These volatiles are reliable indicators of host presence when their emission in plants is induced by herbivory. Hyperparasitoids may also use information from lower trophic levels to locate their parasitoid hosts but little is known about the role of volatiles from the plant–host complex in the foraging behavior of hyperparasitoids. Here, we studied how Dendrocerus aphidum (Megaspilidae) responds to plant and host volatiles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 31 publications
0
4
0
2
Order By: Relevance
“…A comparative study on four species of aphid-associated hyperparasitoids concluded that contact cues of mummies and honeydew were more important than olfactory cues in hyperparasitoid host location (10). In contrast, a laboratory study recently showed that female Dendrocerus aphidum are attracted to volatiles from the plant-host complex, but this attraction was likely due to the presence of mummies and not to (induced) plant volatiles (24). Moreover, when attractive mummy hosts were presented in combination with plants, D. aphidum no longer preferred the smell of mummies, suggesting that plant volatiles may confuse foraging hyperparasitoids.…”
Section: Plant Volatiles As Foraging Cuesmentioning
confidence: 99%
See 2 more Smart Citations
“…A comparative study on four species of aphid-associated hyperparasitoids concluded that contact cues of mummies and honeydew were more important than olfactory cues in hyperparasitoid host location (10). In contrast, a laboratory study recently showed that female Dendrocerus aphidum are attracted to volatiles from the plant-host complex, but this attraction was likely due to the presence of mummies and not to (induced) plant volatiles (24). Moreover, when attractive mummy hosts were presented in combination with plants, D. aphidum no longer preferred the smell of mummies, suggesting that plant volatiles may confuse foraging hyperparasitoids.…”
Section: Plant Volatiles As Foraging Cuesmentioning
confidence: 99%
“…Pseudo-hyperparasitoids that oviposit on the (pre)pupal stage of their host may use information from the pupal skin or cocoon. Dendrocerus carpenteri and D. aphidum are attracted to aphid mummies, and Siri (102) showed that long-chain compounds may mediate this response, at least at short-range, while de Boer et al (24) showed that mummies can attract D. aphidum over a longer distance as well, suggesting that volatile compounds may be involved too (but see above). After arrival on a plant, aphid-associated hyperparasitoids may be arrested by the presence of honeydew (9), possibly because it is an important food source for them (25).…”
Section: Close Range Foraging Cuesmentioning
confidence: 99%
See 1 more Smart Citation
“…Eén aspect is dat predatoren en parasitoïden ook elkaar bestrijden. Hyperparasitoïden zijn hiervan een voorbeeld die in de kasteelt voor behoorlijke reductie kunnen zorgen van de parasitoïden van bladluizen (De Boer et al, 2020). Hetzelfde geldt voor grotere soorten loopkevers die kleinere soorten eten en zodoende de natuurlijke vijand van bijvoorbeeld Delia vliegen reduceren (Prasad en Snyder, 2004).…”
Section: Mijten En Sluipwespenunclassified
“…De hyperparasitoïde voedt zich op de pop van de primaire parasitoïde en voorkomt zo de populatiegroei van de primaire parasitoïde. Onderzoek naar hyperparasitoïden richt zich op dit moment op de kasteelt van paprika waar ze voor aanzienlijke reductie van de primaire parasitoïde kunnen zorgen (de Boer et al, 2020).…”
Section: Seksferomonenunclassified